KAZAKH-JAPANESE PARTNERSHIP IN THE FORMAT OF "CENTRAL ASIA PLUS JAPAN" (Journal of Oriental Studies, 2025)
The purpose of the study is to examine the results of projects implemented within the framework of the Kazakh-Japanese partnership in the format of "Central Asia plus Japan". In 2005, in accordance with this concept of dialogue, the Japan Bank for International Cooperation (JBIC) also conducted a study of water resources and electricity, which is one of the main cores of this mechanism, in order to study the form of promoting intraregional cooperation.In the course of research on this topic, comprehensive theoretical research methods methods of comparison, differentiation, generalization, systematization used. In the course of the study of strategic cooperation between Kazakhstan and Japan, the scientific works of famous domestic scientists were considered: T. Dadabaev, A. Duisekov, A. Bitabarova, G. Duisen, N. Kasenova.  The research works of foreign researchers were also used: Yu. Takeshi, D. Kitade, T. Caparella, B. Dave.The relevance of the study lies in the fact that 2 – At the meeting of the Ministers of Foreign Affairs held in 2006, the then Minister of Foreign Affairs of Japan, Mr. Aso, who was Chairman and other honorary participants: the Ministers of Foreign Affairs of Kyrgyzstan, Tajikistan and Uzbekistan and the Ambassador on special assignments of Kazakhstan adopted an "action plan" defining specific directions and signed for 5 areas developed A framework for political dialogue, development of intraregional cooperation, promotion of business, intellectual dialogue, cultural ties and people exchange.In this "action plan", "Water and energy issues" are recognized as one of the most important sectors that can make a special contribution to the work of providing assistance for intraregional cooperation. In order to carry out intraregional cooperation activities within the framework of the "action plan", the Central Asian countries must actively act and build trusting relationships.Keywords: strategic cooperation, dialogue of Central Asia plus Japan, Kazakhstan, Japan, contract.